Disentangling input and output-related components of spatial neglect - Loetscher, Tobias; Nicholls, Michael E.; Brodtmann, Amy; Thomas, Nicole A.; Brugger, Peter (Frontiers in Human Neuroscience, 2012)
Spatial neglect is a heterogeneous disorder with a multitude of manifestations and subtypes. Common clinical neglect tests fail to differentiate these subtypes. In line bisection tasks, for example, a marked rightward deviation can be caused by an underestimation of the left half of the line (input-related deficit), by the failure to direct actions towards the left side of space (output-related deficit), or by a mixture of both these impairments. To disentangle these components, we used a test consisting of a line bisection task on a touch screen monitor (manual motor task) and the subsequent judgment of one's own bisection performance (visual perceptual task). It is hypothesized that patients with mainly output-related neglect should be better in recognizing their misbisected lines than patients with purely input-related neglect. In a group of 16 patients suffering from spatial neglect, we found that patients are three times more likely to suffer from a predominantly input-related than from an output-related subtype. The results thus suggest that neglect is typically an input-related impairment. Additional analysis of the line bisection task revealed that temporal (slowness in initiation and execution of contralateral movements) and spatial (insufficient movement amplitude towards the contralesional side) aspects of output-related neglect were not related. This independence raises the possibility that a fine-grained differentiation of output-related neglect is required. That is, impairments in lateralized temporal and spatial aspects of movements may underlie different neglect subtypes.